Genetic association analysis with R - Zhao, Jing Hua (Henry Stewart Talks, 2009)
R environment for statistical analysis, Rationale of R for genetic data, Use of packages, Haplotype analysis, Regional association, The Framingham data, GenABEL, Q-Q and Manhattan plots, GWAS, Issues and challenges, Meta-analysis, Use of publically available data, A technical summary